2012
DOI: 10.1002/star.201100176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maillard reaction products prepared from glucose–glycine model systems on starch digestibility

Abstract: The Maillard reaction is one of the most important phenomena occurring spontaneously during food processing and storage. However, research on the effects of Maillard reaction products (MRPs) on starch hydrolysis remains insufficient. To investigate the effects of MRPs on in vitro starch digestibility, the characteristics of glucose–glycine model system containing MRPs and digestive enzyme activities by MRPs were measured. MRPs were prepared by heating of glucose–glycine mixture solution at 90°C for different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Maillard reactions occur between amino acids and reducing sugars under a suitable temperature that normally needs to be above 50 ∘ C and it can be stimulated when moisture diminishes. The Maillard reaction efficiency depends upon various factors including chemical conformation of proteins, amino acid residues, and presence of reducing sugars and of complex carbohydrates such as starch [19].…”
Section: Cookies Physicochemical Characteristicsmentioning
confidence: 99%
“…Maillard reactions occur between amino acids and reducing sugars under a suitable temperature that normally needs to be above 50 ∘ C and it can be stimulated when moisture diminishes. The Maillard reaction efficiency depends upon various factors including chemical conformation of proteins, amino acid residues, and presence of reducing sugars and of complex carbohydrates such as starch [19].…”
Section: Cookies Physicochemical Characteristicsmentioning
confidence: 99%
“…Amino acids and reducing sugars usually produced a Maillard reaction at temperatures above 50 °C and in less humid conditions. The Maillard reaction efficiency depended on a variety of factors, including the chemical conformation of the protein, the presence type of amino acid residues, reducing sugars, and complex carbohydrates (starch) (Chung, Han, Lee, & Rhee, ).…”
Section: Resultsmentioning
confidence: 99%
“…The rats in this study were fasted for 6 h prior to the sacrifice; thus, it was reasonable that lower digestive enzyme activities were measured in the rats. Furthermore, it was also found that the activities of digestive enzymes such as carboxypeptidase, aminopeptidase, and α-amylase were inhibited by the Maillard reaction product from various reaction systems, while trypsin extracted from the anterior intestine also could be inhibited by the melanoidins [ 42 , 43 , 44 ]. The three studies thus provided result support to the present study.…”
Section: Discussionmentioning
confidence: 99%